Neglecting Plasma Protein Binding in COVID‐19 Patients Leads to a Wrong Interpretation of Lopinavir Overexposure. Issue 4 (9th March 2021) - Stanke‐Labesque, Francoise; Concordet, Didier; Djerada, Zoubir; Bouchet, Stéphane; Solas, Caroline; Mériglier, Etienne; Bonnet, Fabrice; Mourvillier, Bruno; Ruiz, Stéphanie; Martin‐Blondel, Guillaume; Epaulard, Olivier; Schwebel, Carole; et al.
Abstract : Boffito et al . recalled the critical importance to correctly interpret protein binding. Changes of lopinavir pharmacokinetics in coronavirus disease 2019 (COVID‐19) are a perfect illustration. Indeed, several studies described that total lopinavir plasma concentrations were considerably higher in patients with severe COVID‐19 than those reported in patients with HIV. These findings have led to a reduction of the dose of lopinavir in some patients, hypothesizing an inhibitory effect of inflammation on lopinavir metabolism. Unfortunately, changes in plasma protein binding were never investigated. We performed a retrospective cohort study. Data were collected from the medical records of patients hospitalized for COVID‐19 treated with lopinavir/ritonavir in intensive care units or infectious disease departments of Toulouse University Hospital (France). Total and unbound concentrations of lopinavir, C reactive protein, albumin, and alpha‐1‐acid glycoprotein (AAG) levels were measured during routine care on the same samples. In patients with COVID‐19, increased total lopinavir concentration is the result of an increased AAG‐bound lopinavir concentration, whereas the unbound concentration remains constant, and insufficient to reduce the severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) viral load. Although international guidelines have recently recommended against using lopinavir/ritonavir to treat severe COVID‐19, the description of lopinavir pharmacokinetics changes in COVID‐19 is a textbook case of the high risk of misinterpretation of a total drug exposure when changes in protein binding are not taken into consideration.